Conhecendo o nanomundo, produzindo nanoartes; uma etnografia das formas a associações emergentes em um laboratório de nanotecnologia - Silva Filho, Maurilio de Jesus (2018)
This ethnography is about the produce of images and senses in the world on nanometric scales in a scientific and technological laboratory. Images that come to life and senses and transformed in artistic artifacts. The Nanoart, imaginative creations that have their root in the images of electronic microscopes, are not merely the matter of study of this work, they also help me as ethnographic guides into my immerging and learning what is going on in a nanotechnology laboratory, named LIEC. The nanoworld, the world occurring in the depths of matter and inhabited by vibrations and atomic particles are explored there, in the dual meaning of this word. Molecules and atoms are embedded by researches in a repeated search for management of the forms and associations of chemical compounds manipulated by the wish of their “masters. Scientific images that are generated by microscopes and spread as visible evidence of a characteristic of the material produced. The later generated arts are a small fraction of these scientific images chosen to become artistic artifacts. They are inserted internal and external to the scientific world into circulation, included into contexts of scientific popularization and disperse in the social environment, acting as elements of perception capture in favor of the worlds on nanoscale, this world that is in a daily interaction with researchers and laboratory technicians.